An epidemiological study of road traffic accidents among patients admitted in a tertiary care hospital in Puducherry - T., Muthukumar; Singh, Zile; Prasad R., Vishnu; Samuel, Abel K.; T. K., Raja (International Journal Of Community Medicine And Public Health, 2018)
Background: Road traffic accidents (RTA) are the only public health problem for which society and decision makers still accept death and disability among young people on a large scale. This study was undertaken to determine the various epidemiological factors influencing RTA with a view to suggest appropriate remedial measures for prevention of accidents. Methods: A hospital based prospective observational study was conducted at a tertiary care hospital in Puducherry. All the patients admitted in the hospital due to RTA from Jan to Dec 2014 were interviewed by using a pre-tested and pre-designed questionnaire. Data was entered in MS Excel and analysed using SPSS version 21.0. Institute ethics committee clearance was obtained. Results: Among 541 participants, 50% of the victims were in the productive age group of 20-40 yrs. The approximate speed of majority of the vehicles (55.6%) at the time of accident was 40-80 km/hr. Among the accident victims, 85.8% of the two wheeler riders did not use helmet and 70.9% of the car drivers did not wear seat belt at the time of accident. Around 39% of the drivers were under the influence of alcohol at the time of accident. Mobile phone is the major cause of distraction (51.9%) at the time of accident. Conclusions: Based on this study it is evident that prevention and control of most of the modifiable factors can bring about a change in the statistics that would ensure our future to be safer.